A Systemized Approach to Investigate Ca2+ Synchronization in Clusters of Human Induced Pluripotent Stem-Cell Derived Cardiomyocytes - Jones, Aled R.; Edwards, David H.; Cummins, Michael J.; Williams, Alan J.; George, Christopher H. (Frontiers in Cell and Developmental Biology, 2016)
Induced pluripotent stem cell-derived cardiomyocytes (IPS-CM) are considered by many to be the cornerstone of future approaches to repair the diseased heart. However, current methods for producing IPS-CM typically yield highly variable populations with low batch-to-batch reproducibility. The underlying reasons for this are not fully understood. Here we report on a systematized approach to investigate the effect of maturation in embryoid bodies (EB) vs. “on plate” culture on spontaneous activity and regional Ca2+ synchronization in IPS-CM clusters. A detailed analysis of the temporal and spatial organization of Ca2+ spikes in IPS-CM clusters revealed that the disaggregation of EBs between 0.5 and 2 weeks produced IPS-CM characterized by spontaneous beating and high levels of regional Ca2+ synchronization. These phenomena were typically absent in IPS-CM obtained from older EBs (>2 weeks). The maintenance of all spontaneously active IPS-CM clusters under “on plate” culture conditions promoted the progressive reduction in regional Ca2+ synchronization and the loss of spontaneous Ca2+ spiking. Raising the extracellular [Ca2+] surrounding these quiescent IPS-CM clusters from 0.4 to 1.8 mM unmasked discrete behaviors typified by either (a) long-lasting Ca2+ elevation that returned to baseline or (b) persistent, large-amplitude Ca2+ oscillations around an increased cytoplasmic [Ca2+]. The different responses of IPS-CM to elevated extracellular [Ca2+] could be traced back to their routes of derivation. The data point to the possibility of predictably influencing IPS-CM phenotype and response to external activation via defined interventions at early stages in their maturation.